PENGEMBANGAN KURIKULUM PRODI PGMI UINSU MEDAN MERUJUK KKNI DENGAN PENDEKATAN TRANSDISIPLIN - Nirwana Anas; Ramadan Lubis (Universitas Negeri Medan, 2021)
Abstract: Curriculum Development of PGMI UINSU Medan Study Program Refers to KKNI with a Transdisciplinary approach. Islamic education is a system in order to create an idealized Muslim figure, namely a master of thought and remembrance (ūlul al-Bāb). Thus, the theory of education that is built must be derived from Islamic teachings as a reference to develop science and values that will be transistorized in educational practice. In realizing quality education, standardization is needed and well-systematized. For this reason, higher education institutions must refer to the curriculum that has been regulated by the government, namely the National curriculum based on KKNI. Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) is one of the Study Programs (Study Programs) that organizes learning activities that refer to KKNI. In addition to implementing KKNI, PGMI also implements a Transdisciplinary curriculum that is characteristic of UIN North Sumatra Medan. This idea of transdisciplinary was born from the change of IAIN to UIN which manages diverse disciplines, namely general sciences and religious sciences. Transdisciplinary is a cross-disciplinary study for the study of one object of study that will produce synthesis, through cooperative efforts, so as to give birth to new knowledge, understanding, and perspectives. This research is development research that aims to produce: (1). Formulation of the KKNI curriculum in the PGMI FITK UIN SU Medan Study Program for the 2018/2019 academic year. (2). Formulation of Transdisciplinary approach in PGMI FITK UIN SU Medan Study Program for the academic year 2018/2019. (3). The results of curriculum development of PGMI study program refer to KKNI with transdisciplinary approach in semester learning plan (RPS) academic year 2018/2019.Keywords: PGMI, Curriculum, KKNI, Transdiscipline.Abstrak: Pengembangan Kurikulum Prodi PGMI UINSU Medan Merujuk KKNI dengan pendekatan Transdisiplin. Pendidikan Islam adalah sebuah sistem dalam rangka mewujudkan sosok Muslim yang diidealkan yakni seorang yang ahli fikir dan zikir (ūlul al-Bāb). Dengan demikian, teori pendidikan yang dibangun harus bersumber dari ajaran Islam sebagai acuan untuk mengembangkan ilmu pengetahuan dan nilai-nilai yang akan ditransinternalisasikan dalam praktek pendidikan. Dalam mewujudkan pendidikan yang berkualitas, dibutuhkan adanya standarisasi dan tersistematisasi dengan baik. Untuk itu lembaga pendidikan tinggi harus mengacu kepada kurikulum yang sudah diatur oleh pemerintah, yaitu kurikulum Nasional yang berbasis KKNI. Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) adalah salah satu Program Studi (Prodi) yang menyelenggarakan kegiatan pembelajaran yang mengacu kepada KKNI. Disamping menerapkan KKNI, PGMI juga menerapkan kurikulum Transdisipliner yang menjadi ciri khas UIN Sumatera Utara Medan. Gagasan Transdisiplin ini terlahir dari perubahan IAIN menjadi UIN yang mengelola disiplin ilmu yang beragam, yaitu ilmu-ilmu umum dan ilmu ilmu agama. Transdisipliner adalah kajian lintas disiplin ilmu untuk kajian satu objek kajian yang akan menghasilkan sintesa, melalui upaya kooperatif, sehingga dapat melahirkan ilmu pengetahuan, pemahaman, dan perspektif baru. Penelitian ini adalah penelitian pengembangan (development research) yang bertujuan untuk menghasilkan: (1). Rumusan kurikulum KKNI di Program Studi PGMI FITK UIN SU Medan tahun akademik 2018/2019. (2). Rumusan pendekatan Transdisiplin di Program Studi PGMI FITK UIN SU Medan tahun akademik 2018/2019. (3). Hasil Pengembangan kurikulum Program Studi PGMI merujuk KKNI dengan pendekatan Transdisiplin dalam Rencana Pembelajaran Semester (RPS) tahun akademik 2018/2019.Kata Kunci: PGMI, Kurikulum, KKNI, Transdisiplin.